(3eNJUQ JPcQI GdeaQOGJs - (3eLghds ((3HGdcQjs)
(3ChdgG (B:s
(3CSJaJM HMeO Gddg agPG cJGH eeG fbdg Yf fMh CQHYeGFI Mcje ef Cgd GdeSCdI GdESdGejI hef GdjhfGf hZjQge ceG SfTjQ Edi LedI ef CSeGFge aj NGJeI GdcJGH hbO PcQ aj NWHI GdJPcQI Cfg eG LeY ajgG EdG eG GSJMSfgs
(3BNQgG (B:s
(3aUd GdeOHhZ ef GdKjGH EPG ZSdJ GdKjHG GdeUHhZI HWHjN GdbWa haQGWhS hcSQi hbQGWjS hgQeS hCWGd aj Pdc GdCUd haj gPG GdbOQ caGjI aj WeCfjfI GdbdH Edi GSJYeGd eG ajg ef GdCOhjIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc ZjQ eDQN d (B: (3GdSjO eMeO dGQfOhjs
Keywords: (3GdWHs